On the Factors Influencing Green Purchase Intention: A Meta-Analysis Approach - Zhuang, Wencan; Luo, Xiaoguang; Riaz, Muhammad Usman (Frontiers in Psychology, 2021)
This study systematically analyzes the factors that affect consumers’ green purchase intention. Through a comprehensive literature review, the influencing factors of consumers’ green purchase intention are organized into three categories: cognitive factors, consumer individual characteristics, and social factors. Next, a meta-analysis of 54 empirical papers was conducted using Comprehensive Meta-Analysis 3.0 software to quantitatively assess these relationships. The results revealed that green perceived value, attitude, and green trust have a significant positive influence on green purchase intention. Perceived behavior control, perceived consumer effectiveness, and subjective norm also has a strong positive impact on green purchase intention. Collectivism has a positive effect on green purchase intention. Green perceived risk has a significant negative impact on green purchase intention. The study’s findings provide references for enterprises engaged in green product diffusion and organizations responsible for environmental protection.